Fine hollow particle produced using supercritical liquid
By using supercritical fluid to remove organic solvents in the production of micro-vacuum particles, and using water in oil (O/W) emulsion method to control particle size and dispersion, the problem of difficult particle resistance and particle size control in the prior art is solved, and the production of large-particle micro-vacuum particles with high efficiency and low crushing rate is achieved.
Patent Information
- Application Number
- JP2022033212
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-03-04
- Publication Date
- 2025-04-09
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, it is difficult to achieve good solvent resistance, heat resistance and particle size control at the same time when producing micro-vacuum particles. Especially in CMP polishing pads, micro-vacuum particles are prone to break during drying, resulting in low yield.
Microvacuum particles with excellent solvent resistance and heat resistance are prepared by removing the intrinsic organic solvent from the microvacuum particles using a supercritical fluid (such as supercritical carbon dioxide), and the particle size and dispersion are controlled by water in oil (O/W) emulsion.
It realizes efficient production of large-particle micro-vacuum particles, with high yield, good mechanical properties and low crushing rate, and is suitable for a variety of application scenarios, such as CMP polishing pads, insoles and thermal insulation materials.
Smart Images

Figure 2025056807000001 
Figure 2025056807000002
Abstract
Description
[Technical field]
[0001] The present invention relates to micro hollow particles produced using a supercritical fluid. [Background technology]
[0002] Microhollow particles are used in many fields such as agricultural chemicals, medicines, fragrances, liquid crystals, adhesives, electronic material parts, and building materials. In particular, in recent years, microhollow particles have been studied for the purpose of providing pores in polyurethane (urea) CMP (Chemical Mechanical Polishing) polishing pads used for wafer polishing. Such microhollow particles are required to have excellent solvent resistance, heat resistance, and further, preferable particle size control. In particular, in the field of CMP polishing pads, monodispersed microhollow particles with a relatively large particle size of about 20 to 50 μm are desired in order to achieve a high polishing rate and flatness at the atomic level. Therefore, Patent Document 1 discloses a method for producing microhollow particles made of melamine resin, a thermosetting resin with excellent heat resistance and solvent resistance.
[0003] Patent Document 2 discloses hollow microballoons for CMP polishing pads, which are made of at least one resin selected from the group consisting of melamine resins, urea resins, and amide resins, and have an average particle size in a specific range.
[0004] Furthermore, as a method for drying fine particles, Patent Document 3 discloses a technique in which fine particles made using a radical polymerizable monomer are dried with supercritical carbon dioxide. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 7-41594 [Patent Document 2] International Publication No. 2021 / 201088 [Patent Document 3] Special Publication 2008 / 523192 Summary of the Invention [Problem to be solved by the invention]
[0006] However, although the method of Patent Document 1 provides excellent heat resistance and solvent resistance, there is a problem in terms of controlling the particle size and its dispersibility.
[0007] The method of Patent Document 2 can obtain large particles, but in the process of removing the organic solvent from inside the fine particles, many of the fine particles are destroyed in the drying process, resulting in a low yield and an industrial problem.
[0008] Patent Document 3 discloses a drying method using supercritical carbon dioxide, but the monomers used are only radical polymerizable monomers, and no reference is made to targets for which supercritical carbon dioxide is used other than those mentioned above, nor is there any disclosure of its effects.
[0009] SUMMARY OF THE PRESENT EMBODIMENTS Accordingly, an object of the present invention is to provide hollow microparticles which have excellent solvent resistance and heat resistance, are highly dispersible, and can be used to easily produce stable large-sized hollow microparticles in a good yield. [Means for solving the problem]
[0010] As a result of intensive research into solving the above-mentioned problems, the inventors have found that by producing fine particles containing an organic solvent inside, and then removing the organic solvent inside the fine hollow particles with a supercritical liquid, it is possible to easily produce large-sized hollow fine particles having excellent solvent resistance and heat resistance with good yield, thereby solving the above-mentioned problems and thereby completing the present invention.
[0011] That is, the present invention relates to the following [1] to [8]. [1] Microhollow particles comprised of a resin membrane made of at least one resin selected from the group consisting of melamine resins, urea resins, amide resins, and urethane (urea) resins, which are obtained by preparing a water-in-oil (O / W) emulsion in which an oil phase containing an organic solvent is the dispersed phase and an aqueous phase is the continuous phase, obtaining microparticles in which the organic solvent is encapsulated inside the microparticles, and then removing the organic solvent from the inside of the microparticles using a supercritical liquid. [2] The hollow microparticles according to [1], wherein the supercritical liquid is supercritical carbon dioxide. [3] The hollow microparticles according to [1] or [2], wherein the hollow microparticles are made of a melamine resin. [4] A cured product comprising the hollow microparticles according to any one of the above items [1] to [3] dispersed in a polyurethane resin. [5] A CMP polishing pad comprising the cured body described in [4]. [6] A method for producing hollow microparticles having a resin film made of at least one resin selected from the group consisting of melamine resins, urea resins, amide resins, and urethane (urea) resins, comprising: preparing a water-in-oil (O / W) emulsion in which an oil phase containing an organic solvent is the dispersed phase and an aqueous phase is the continuous phase; obtaining microparticles having an organic solvent encapsulated therein; and then removing the organic solvent from the interior of the microparticles using a supercritical liquid. [7] A method for producing hollow microparticles composed of a resin film made of a melamine-based resin, comprising: a first step: (a) a step of preparing an oil phase containing an organic solvent; a second step: (b) a step of preparing an aqueous phase containing at least one surfactant made of a maleic anhydride copolymer; a third step: a step of mixing and stirring the oil phase and the aqueous phase to prepare a water-in-oil (O / W) emulsion in which the aqueous phase is a continuous phase and the oil phase is a dispersed phase; and a fourth step: a step of adding a melamine formaldehyde prepolymer compound to the water-in-oil (O / W) emulsion to cause condensation of the melamine formaldehyde prepolymer compound on the interface of the water-in-oil (O / W) emulsion. a fifth step: a step of separating the microparticles having the organic solvent encapsulated therein from the microparticle dispersion; and a sixth step: a step of removing the organic solvent from the interior of the microparticles using supercritical carbon dioxide to obtain hollow microparticles, wherein the weight ratio of the (a) oil phase containing an organic solvent to the (b) aqueous phase containing a surfactant made of at least one type of maleic anhydride copolymer is 100 to 500 parts by mass when the (a) component is taken as 100 parts by mass. [8] The method for producing hollow microparticles according to [7], wherein the organic solvent used in the (a) oil phase is selected from organic solvents having a boiling point of 100°C to 180°C. Effect of the Invention
[0012] The hollow fine particles of the present invention have excellent solvent resistance and heat resistance, and it is possible to easily obtain large-sized hollow fine particles in good yield by removing the organic solvent inside the hollow fine particles with a supercritical fluid.
[0013] The hollow microparticles of the present invention can be used in a variety of applications, including, for example, agricultural chemicals, medicines, cosmetic materials, liquid crystals, adhesives, electronic material parts, building materials, etc. In particular, the hollow microparticles of the present invention can be used in shoe soles and insoles, heat insulating materials, sound insulating materials, CMP polishing pads, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The hollow microparticles of the present invention are composed of a resin film made of at least one resin selected from the group consisting of melamine resins, urea resins, amide resins, and urethane (urea) resins, and preferably have an average particle size of 1 to 100 μm. The hollow microparticles are obtained by preparing a water-in-oil (O / W) emulsion (hereinafter also referred to as "O / W emulsion") in which an oil phase containing an organic solvent is the dispersed phase and an aqueous phase is the continuous phase, obtaining microparticles in which an organic solvent is encapsulated inside the microparticles, and then removing the organic solvent from the inside of the microparticles using a supercritical liquid.
[0015] In the present invention, the melamine resin is a resin whose main chain is obtained by polycondensation of a polyfunctional amine containing melamine and formaldehyde, the urea resin is a resin whose main chain is obtained by polycondensation of urea (including a polyfunctional amine) and formaldehyde, the amide resin is a resin whose main chain has an amide bond, and the urethane (urea) resin is a resin whose main chain has a urethane bond, a urea bond, or both a urethane bond and a urea bond in the main chain, which are obtained by reaction of an isocyanate group with a hydroxyl group and / or an amino group.
[0016] Examples of supercritical liquids that can be used in the present invention include carbon dioxide, nitrogen dioxide, ethane, ethylene, oxygen, and nitrogen, and preferably carbon dioxide. Here, the term "supercritical liquid" refers to a substance that, when in a supercritical state exceeding the critical temperature and critical pressure, has a density close to that of a liquid and a low viscosity like a gas, and is in an intermediate state between a liquid and a gas. The supercritical temperatures and supercritical pressures at which the above-mentioned carbon dioxide, nitrogen, ethane, ethylene, propane, and oxygen are in a supercritical state are carbon dioxide (31°C, 7.4MPa), nitrogen (-147°C, 3.4MPa), ethane (32°C, 4.9MPa), ethylene (9.2°C, 5.0MPa), propane (97°C, 4.2MPa), and oxygen (-118°C, 5.1MPa).
[0017] Generally, when forming an emulsion, large emulsions exceeding a few tens of micrometers are unstable, and after forming microparticles of a few tens of micrometers, the microparticles tend to crack during the process of removing the organic solvent from inside the microparticles, or to shrink due to the loss of internal liquid, resulting in a low yield.
[0018] In the present invention, by using a supercritical liquid that has excellent solubility close to that of a liquid and excellent diffusibility close to that of a gas, and therefore has high solubility in resin and a high diffusion rate in resin, it is possible to replace and remove the organic solvent inside the microparticles in a short time. In addition, by returning the supercritical liquid from the supercritical state to a gas state while the supercritical liquid is contained inside the microparticles, it is possible to retain the gas inside the microhollow particles, and as a result, it is presumed that it is possible to obtain microhollow particles with a high yield even from large emulsions exceeding several tens of μm.
[0019] As described above, the hollow microparticles of the present invention are formed of a resin film made of at least one resin selected from the group consisting of melamine resin, urea resin, amide resin, and urethane resin. Among these, the preferred resin in the present invention is melamine resin.
[0020] The average particle diameter of the hollow microparticles of the present invention is preferably 1 to 100 μm. With this range, for example, when the hollow microparticles are mixed into a CMP polishing pad, excellent polishing properties can be exhibited. More preferably, the average particle diameter of the hollow microparticles is 5 to 80 μm, and most preferably, 10 to 50 μm.
[0021] The average particle size of the hollow microparticles can be measured by a known method, specifically, by using an image analysis method. The particle size can be easily measured by using the image analysis method. The average particle size is the average particle size of primary particles. The average particle size can be measured by the image analysis method, for example, using a scanning electron microscope (SEM).
[0022] The bulk density of the hollow microparticles of the present invention is not particularly limited, but is preferably 0.01 to 0.5 g / cm. 3 When the molecular weight falls within this range, the material can be suitably used, for example, for heat insulating materials and CMP polishing pad applications.
[0023] The ash content of the micro hollow particles of the present invention is not particularly limited, but in the method described in the following examples, it is preferably 0.5 mass parts or less, more preferably 0.3 mass parts or less, more preferably 0.1 mass parts or less, and most preferably not measured, per 100 mass parts of the micro hollow particles.By being in this range, when used in CMP polishing pad, it is possible to reduce wafer defects.
[0024] The method for producing hollow microparticles of the present invention is a production method in which, in a step of obtaining microparticles, an O / W emulsion is prepared in which an oil phase containing an organic solvent is the dispersed phase and an aqueous phase is the continuous phase, thereby obtaining microparticles in which an organic solvent is encapsulated inside the microparticles, and the organic solvent is removed from the inside of the microparticles using a supercritical liquid.
[0025] The method for forming a resin film in an O / W emulsion of hollow microparticles can be broken down into the following steps: first step: (a) a step of preparing an oil phase (hereinafter also referred to as "component (a)") containing an organic solvent to which a component for forming a resin film has been added as necessary; second step: (b) a step of preparing an aqueous phase (hereinafter also referred to as "component (b)") containing a surfactant; third step: a step of mixing and stirring component (a) and component (b) to prepare an O / W emulsion in which the aqueous phase is a continuous phase and the oil phase is a dispersed phase; The process is divided into four steps: a fourth step is a step of adding components that constitute a resin film into the O / W emulsion, and causing a condensation reaction on the interface of the O / W emulsion to form a resin film to form microparticles, thereby obtaining a microparticle dispersion in which the microparticles having an organic solvent encapsulated therein are dispersed; a fifth step is a step of separating the microparticles having an organic solvent encapsulated therein from the microparticle dispersion; and a sixth step is a step of removing the organic solvent solution from the interiors of the microparticles using a supercritical liquid to form hollow microparticles.
[0026] When the hollow microparticles are formed of a resin film made of melamine resin, they are produced by the following process.
[0027] 1st step: The first step is to prepare an oil phase (a) containing an organic solvent, which will be the dispersed phase in the O / W emulsion. In this step, it is possible to include substances other than the organic solvent, but the oil phase is usually composed of only the organic solvent.
[0028] Second step: The second step is a step of preparing (b) an aqueous phase containing a surfactant, which becomes the continuous phase in the O / W emulsion, and adjusting the pH as necessary.
[0029] This step includes dissolving a surfactant, which will be described later, in water and adjusting the pH, if necessary. The pH adjustment and the like may be carried out by using a known method.
[0030] In the present invention, the amount of the surfactant used is preferably 0.1 to 10% based on the aqueous phase, and more preferably 1 to 10%. Within this range, aggregation of droplets of the dispersed phase in the O / W emulsion is avoided, and hollow microparticles can be easily obtained with good yield.
[0031] Third step: The third step is a step of mixing and stirring the component (a) obtained in the first step and the component (b) obtained in the second step to prepare an O / W emulsion in which the component (a) constitutes the continuous phase and the component (b) constitutes the dispersed phase.
[0032] In the present invention, the method of mixing and stirring the components (a) and (b) to prepare an O / W emulsion can be adjusted by mixing and stirring them by a known method, taking into consideration the particle size of the hollow microparticles to be produced. Furthermore, the temperature and pH can also be adjusted in the process of preparing the O / W emulsion.
[0033] Among them, a method of mixing the (a) component and the (b) component, and then dispersing the mixture using a known dispersing machine such as a high-speed shear type, friction type, high-pressure jet type, or ultrasonic type for stirring, to prepare an O / W emulsion is preferably adopted, and among these, a high-speed shear type is preferred. When using a high-speed shear type dispersing machine, the rotation speed is preferably 500 to 20,000 rpm, more preferably 1,000 to 10,000 rpm. The dispersion time is preferably 0.1 to 30 minutes, and preferably 1 to 10 minutes. The dispersion temperature is preferably 20 to 80°C.
[0034] In the present invention, the weight ratio of the component (a) to the component (b) is preferably such that the component (b) is 100 to 500 parts by mass, and more preferably 150 to 300 parts by mass, per 100 parts by mass of the component (a).
[0035] 4th step: The fourth step is a step of adding a melamine formaldehyde prepolymer compound to the O / W emulsion to cause a condensation reaction of the melamine formaldehyde prepolymer compound at the interface of the O / W emulsion to form a resin film, thereby forming microparticles with an organic solvent encapsulated inside, and obtaining a microparticle dispersion in which the formed microparticles are dispersed.
[0036] The amount of the melamine formaldehyde prepolymer compound used is not particularly limited, but in order to form fine particles well, it is preferably 20 to 100 parts by mass per 100 parts by mass of the component (a) used in the first step.
[0037] As the melamine formaldehyde prepolymer compound, a commercially available melamine formaldehyde prepolymer compound described later may be added as it is, or may be dissolved in water or an alkaline aqueous solution before use. Alternatively, a melamine formaldehyde prepolymer compound produced in an alkaline aqueous solution containing melamine and formaldehyde by addition reaction of melamine with formaldehyde upon heating in the alkaline range according to a conventional method may also be used.
[0038] When the melamine formaldehyde prepolymer compound is taken as 100 parts by mass, the water or alkaline aqueous solution is preferably used in an amount of 0 to 500 parts by mass, and more preferably in an amount of 20 to 300 parts by mass.
[0039] The pH of the aqueous phase, which is the continuous phase, may be adjusted after the melamine formaldehyde prepolymer compound is added. The pH of the aqueous phase, which is the continuous phase, is preferably less than 7, more preferably adjusted to 3.5 to 6.5, and most preferably adjusted to 3.5 to 5.5. The reaction is preferably carried out at a reaction temperature in the range of 40 to 90°C. The reaction time is preferably in the range of 1 to 48 hours.
[0040] Fifth step: The fifth step is a step of separating the microparticles having the organic solvent encapsulated therein from the microparticle dispersion. The method for separating the microparticles having the organic solvent encapsulated therein from the microparticle dispersion is not particularly limited and may be selected from general separation techniques, and specifically, filtration, centrifugation, etc. are used.
[0041] 6th step: The sixth step is a step of removing the oil phase from the microparticles obtained in the fifth step in which the organic solvent is enclosed, using a supercritical liquid, to obtain hollow microparticles. A known method for removing the organic solvent from the inside with a supercritical liquid can be used. For example, it is preferable to replace the organic solvent in the inside with a supercritical liquid by flowing the supercritical liquid at a flow rate of 1 mL / min to 200 mL / min for 10 min to 720 min under conditions of the supercritical temperature and supercritical pressure of the supercritical liquid or higher in the presence of the microparticles. After the replacement, the pressure is reduced and the temperature is returned to room temperature to obtain hollow microparticles. When the microparticles contain a large amount of water, it is possible to efficiently remove the water and oil phase by flowing a hydrophilic solvent together with the supercritical liquid, or by forming the microparticles into a slurry with a hydrophilic solvent, or by pretreating the microparticles by decantation or filtration.
[0042] In the present invention, the preferred supercritical liquid is supercritical carbon dioxide, and the preferred conditions for using supercritical carbon dioxide are 40° C. to 90° C. and 16 MPa to 40 MPa.
[0043] Each component is described below.
[0044] In the present invention, the organic solvent used in component (a) is not particularly limited, but is preferably an organic solvent having a boiling point of 90° C. to 200° C. In this range, the formation of an emulsion can be maintained even at the polymerization temperature, and the organic solvent is preferably easily removed from the obtained microparticles.
[0045] More preferably, the boiling point is 100° C. to 180° C. Examples of these include the following.
[0046] Examples of the hydrocarbon solvent that can be used include aliphatic hydrocarbons having 7 to 11 carbon atoms, alicyclic hydrocarbons such as cycloheptane and cyclooctane, butyl acetate, dibutyl ether, 1,2-dichloroethane, toluene, xylene, benzaldehyde, chlorobenzene, and dichlorobenzene.
[0047] These organic solvents may be used alone or in combination of two or more kinds.
[0048] The organic solvent used in the present invention is preferably an aliphatic hydrocarbon having 8 to 11 carbon atoms, cycloheptane, cyclooctane, toluene, xylene, or chlorobenzene, and more preferably toluene, xylene, or chlorobenzene.
[0049] In the present invention, the surfactant used in the component (b) is not particularly limited, and two or more types may be mixed. As a specific example of the surfactant of the present invention, the compounds described in International Publication No. WO2021 / 201088 can be used. Among them, in the case of the component (b) in which the fine hollow particles are made of a melamine resin, those having a carboxyl group as at least one type of hydrophilic group are suitable, and the carboxyl group may be generated by hydrolysis of a dicarboxylic acid anhydride. Among them, maleic anhydride copolymers such as styrene-maleic anhydride copolymer, ethylene-maleic anhydride copolymer, and isobutylene-maleic anhydride copolymer can be preferably used, and more preferably, styrene-maleic anhydride copolymer can be preferably used. In addition, the molecular weight of the maleic anhydride copolymer described above is preferably about 30,000 to 500,000, and most preferably about 100,000 to 500,000. Within this range, a stable emulsion and a resin film can be formed.
[0050] The melamine formaldehyde prepolymer compound that can be used in the present invention can be produced from melamine and formaldehyde according to a conventional method. For example, it can be produced by adding formaldehyde to melamine in an alkaline aqueous solution containing melamine and formaldehyde by heating in the alkaline region. In addition, commercially available melamine formaldehyde prepolymer compounds can also be used as appropriate. For example, Beckamine APM, Beckamine M-3, Beckamine M-3(60), Beckamine MA-S, Beckamine J-101, Beckamine J-1 01LF (manufactured by DIC Corporation), Nika Resin S-176, Nika Resin S-260 (manufactured by Nippon Carbide Corporation), Milben Resin SM-800 (manufactured by Showa Polymer Co., Ltd.), etc. can be mentioned.
[0051] The mechanism of the formation of the hollow microparticles is considered to be that droplets of an oil phase containing (a) an organic solvent are dispersed in an aqueous phase, and the methylolated melamine contained in the melamine formaldehyde prepolymer compound forms an acid amide bond with the hydrophilic group (e.g., carboxyl group) of the surfactant coordinated on the droplet interface, so that the methylolated melamine surrounds the droplets, and in this surrounding state, adjacent methylolated melamines undergo a dehydration condensation reaction between the methylol groups to form a resin film made of a melamine-based resin. In addition, the methylolation ratio of melamine (the molar ratio of formaldehyde to melamine) is related to the density of the resin film, and the higher the methylolation ratio, the higher the crosslinking density and the denser the film. Therefore, it is preferable to use methylolated melamine within the range described below as the methylolated melamine.
[0052] The molar ratio of melamine to formaldehyde can be adjusted from monomethylolated melamine (melamine / formaldehyde molar ratio: 1 / 1) to hexamethylolated melamine (1 / 6). From the standpoint of both the ability to surround the oil phase droplets in the O / W emulsion and condensation reactivity (crosslinking ability), trimethylolated melamine (1 / 3) to pentamethylolated melamine (1 / 5) are preferred, with tetramethylolated melamine (1 / 4) being particularly preferred.
[0053] Even when the hollow microparticles of the present invention are composed of a resin film made of a urea resin, an amide resin, and a urethane (urea) resin, they may be produced by preparing an O / W emulsion and using a known method for obtaining microparticles having an organic solvent encapsulated inside the microparticles.
[0054] In the case of urea resin, it can be produced by the same manufacturing method as the melamine-based resin described above, and can be produced in the same manner by using urea formaldehyde prepolymer instead of the melamine formaldehyde prepolymer compound in the fourth step of the melamine-based resin described above.
[0055] The urea-formaldehyde prepolymer compound is a urea-formaldehyde initial condensation product of urea and formaldehyde, and can be produced according to a conventional method. Examples of the urea-formaldehyde initial condensation product of urea and formaldehyde include methylol urea. In addition, as the urea-formaldehyde prepolymer compound, commercially available products can be appropriately used. For example, 8HSP (manufactured by Showa Polymer Co., Ltd.) can be mentioned.
[0056] When the hollow microparticles are formed of a resin film made of an amide resin, they are produced by the following process.
[0057] 1st step: The first step is to prepare an oil phase (hereinafter also referred to as "component (a2)") which contains (a2) a polyfunctional carboxylic acid compound having at least two carboxyl groups and an organic solvent and which will become the dispersed phase in the O / W emulsion.
[0058] The component (a2) in this step is a step of dissolving a polyfunctional carboxylic acid compound having at least two carboxyl groups in the organic solvent exemplified in the component (a) described above to form an oil phase, and it is sufficient to dissolve it by a known method to form a uniform solution. The amount of the polyfunctional carboxylic acid compound having at least two carboxyl groups used is preferably 0.1 to 50 parts by mass, preferably 0.5 to 20 parts by mass, and more preferably 1 to 10 parts by mass, per 100 parts by mass of the organic solvent. Furthermore, when the mole number (n1) of the carboxylic acid group contained in the polyfunctional carboxylic acid compound having at least two carboxyl groups is the total mole number of amino group-containing compounds of the polyfunctional amine compound having at least two amino groups, the range of 0.5≦(n1) / (n2)≦2 is preferable.
[0059] Furthermore, a catalyst, which will be described later, may be added to the component (a2) for the purpose of promoting the interfacial polymerization reaction.
[0060] Second step: The second step is a step of preparing (b2) an aqueous phase containing a surfactant (hereinafter also referred to as "component (b2)"), which becomes the continuous phase in the O / W emulsion.
[0061] This step is a step in which a surfactant, which will be described later, is dissolved in water to form an aqueous phase, and the surfactant may be dissolved by a known method to form a homogeneous solution.
[0062] In the present invention, the amount of the surfactant used is preferably 0.01 to 20% by mass, more preferably 0.1 to 10% by mass, relative to 100 parts by mass of the aqueous phase. Within this range, aggregation of droplets of the dispersed phase in the O / W emulsion is avoided, and fine particles with a uniform average particle size are easily obtained.
[0063] Furthermore, a catalyst, which will be described later, may be added to the component (b2) for the purpose of promoting the interfacial polymerization reaction.
[0064] Third step: The third step is a step of mixing and stirring the component (a2) obtained in the first step and the component (b2) obtained in the second step to prepare an O / W emulsion in which the component (b2) constitutes the continuous phase and the component (a2) constitutes the dispersed phase.
[0065] In the present invention, the method of mixing and stirring the component (a2) and the component (b2) to prepare an O / W emulsion can be carried out by mixing and stirring them by an appropriate known method, taking into consideration the particle size of the microparticles to be produced.
[0066] Among them, a method of mixing the (a2) component with the (b2) component, and dispersing the mixture using a known dispersing machine such as a high-speed shear type, friction type, high-pressure jet type, or ultrasonic type for stirring, to prepare an O / W emulsion is preferably adopted, and among these, a high-speed shear type is preferred. When using a high-speed shear type dispersing machine, the rotation speed is preferably 500 to 20,000 rpm, more preferably 1,000 to 10,000 rpm. The dispersion time is preferably 0.1 to 60 minutes, and preferably 0.5 to 30 minutes. The dispersion temperature is preferably 10 to 40°C.
[0067] In the present invention, the weight ratio of the (a2) component to the (b2) component is preferably 100 to 1000 parts by mass, and more preferably 150 to 500 parts by mass, per 100 parts by mass of the (a2) component. Within this range, a good emulsion can be obtained.
[0068] 4th step: The fourth step is to add a polyfunctional amine compound having at least two amino groups to the O / W emulsion, and cause interfacial polymerization at the interface of the O / W emulsion to form a resin film, which is then converted into microparticles, thereby obtaining a microparticle dispersion in which the microparticles are dispersed. The amount of the polyfunctional amine compound having at least two amino groups used is as described above.
[0069] Furthermore, when a polyfunctional amine compound having at least two amino groups is added to an O / W emulsion, it may be added as is or may be dissolved in water beforehand.
[0070] When the polyfunctional amine compound having at least two amino groups is dissolved in water in advance, it is preferable to use water in an amount of 50 to 10,000 parts by mass, based on 100 parts by mass of the total amount of the polyfunctional amine compound having at least two amino groups.
[0071] The polymerization temperature is not particularly limited as long as the O / W emulsion is not destroyed, and the reaction is preferably carried out in the range of 5 to 70° C. The polymerization time is also not particularly limited as long as microballoons can be formed, and is usually selected from the range of 0.5 to 24 hours.
[0072] 5th process, 6th process The fifth and sixth steps are similar to those in the case where the hollow microparticles are constituted by a resin film made of a melamine-based resin.
[0073] Here, specific examples of the polyfunctional carboxylic acid compound having at least two carboxyl groups in the component (a2) and the polyfunctional amine having at least two amino groups in the additive phase include the compounds described in International Publication No. WO2021 / 201088. Among them, aromatic dicarboxylic acid dichlorides are suitable as polyfunctional carboxylic acid compounds having at least two carboxyl groups, and most preferably isophthalic acid dichloride and terephthalic acid dichloride. Among the surfactants that can be used in the component (b2), it is preferable to use a sodium acrylate-acrylic acid ester copolymer.
[0074] When the hollow microparticles are formed of a resin film made of a urethane resin, they are produced by the following process.
[0075] 1st step: The first step is to prepare an oil phase (hereinafter also referred to as "component (a3)") which contains a polyfunctional isocyanate compound having at least two isocyanate groups (a3) and an organic solvent and which becomes a dispersed phase in the O / W emulsion.
[0076] The component (a3) in this step is a step of dissolving an isocyanate compound having at least two isocyanate groups in the organic solvent exemplified in the component (a) described above to form an oil phase, and it is sufficient to dissolve it by a known method to form a uniform solution. The amount of the polyfunctional isocyanate compound having at least two isocyanate groups used is 0.1 to 50 parts by mass, preferably 0.5 to 20 parts by mass, and more preferably 1 to 10 parts by mass, relative to 100 parts by mass of the organic solvent. Furthermore, when the mole number (n1) of the isocyanate group contained in the polyfunctional isocyanate compound having at least two isocyanate groups and the mole number (n2) of the total active hydrogen group contained in the polyol, polyamine, and active hydrogen-containing compound having both a hydroxyl group and an amino group, are preferably in the range of 0.5≦(n1) / (n2)≦2.
[0077] Furthermore, a catalyst, which will be described later, may be added to the component (a3) for the purpose of promoting the interfacial polymerization reaction.
[0078] Second step: The second step is to prepare an aqueous phase (b3) containing a surfactant and water (hereinafter also referred to as "component (b3)"), which will be the continuous phase in the O / W emulsion. The preparation method can be the same as that for component (b2) described above.
[0079] 3rd process The third step is the same as the step in which the hollow fine particles are constituted by a resin film made of an amide resin.
[0080] 4th step: The fourth step is a step of adding at least one selected from polyol, polyamine, and active hydrogen-containing compound having both hydroxyl group and amino group to the O / W emulsion, and forming a resin film by interfacial polymerization on the interface of the O / W emulsion to form fine particles, thereby obtaining a fine particle dispersion in which the fine particles are dispersed. The amount of the at least one selected from polyol, polyamine, and active hydrogen-containing compound having both hydroxyl group and amino group to be used is 0.001 to 100 parts by mass, preferably 0.01 to 80 parts by mass, and more preferably 0.01 to 50 parts by mass, based on 100 parts by mass of the organic solvent used in the first step.
[0081] In addition, polyols, polyamines, and active hydrogen-containing compounds having both hydroxyl groups and amino groups are compounds that are at least partially soluble in water and have a higher affinity for hydrophilic phases than for hydrophobic phases, and generally have a solubility of at least 1 g / L in hydrophilic solvents such as water at room temperature, and preferably water-soluble compounds having a solubility of 20 g / L or more in hydrophilic solvents can be selected.
[0082] When polyols, polyamines, and active hydrogen-containing compounds having both hydroxyl groups and amino groups are added to an O / W emulsion, they may be added as they are or may be dissolved in water beforehand.
[0083] When dissolving in water in advance, it is preferable to use water in an amount of 50 to 10,000 parts by mass when the total amount of the polyol, polyamine, and active hydrogen-containing compound having both a hydroxyl group and an amino group is 100 parts by mass.
[0084] The polymerization temperature is not particularly limited as long as the O / W emulsion is not destroyed, and the reaction is preferably carried out in the range of 5 to 70° C. The polymerization time is also not particularly limited as long as fine particles can be formed, and is usually selected from the range of 0.5 to 24 hours.
[0085] 5th process, 6th process The fifth and sixth steps are similar to those in the case where the hollow microparticles are constituted by a resin film made of a melamine-based resin.
[0086] Here, specific examples of the polyfunctional isocyanate compound having at least two isocyanate groups in the component (a3), polyol, polyamine, and active hydrogen-containing compound having both a hydroxyl group and an amino group include the compounds described in International Publication No. WO2021 / 065625.
[0087] Among these, as the polyfunctional isocyanate compound, from the viewpoint of controlling the strength and reactivity of the formed microparticles, preferred are alicyclic isocyanates selected from isophorone diisocyanate, 1,3-bis(isocyanatemethyl)cyclohexane, and (bicyclo[2.2.1]heptane-2,5(2,6)-diyl)bismethylene diisocyanate, aromatic isocyanates selected from 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate (o-, m-, p-), polyfunctional isocyanates having a biuret structure, uretdione structure, or isocyanurate structure, which are mainly made from diisocyanates such as hexamethylene diisocyanate or tolylene diisocyanate, and polyfunctional isocyanates as adducts with trifunctional or higher polyols.
[0088] In addition, examples of polyols, polyamines, and active hydrogen-containing compounds having both a hydroxyl group and an amino group include bifunctional polyols such as ethylene glycol, diethylene glycol, propylene glycol, neopentyl glycol, 1,2-butanediol, 1,3-butanediol, 2,3-butanediol, and 1,4-butanediol; trifunctional polyols such as glycerin, trimethylolethane, and trimethylolpropane; pentaerythritol, erythritol, diglycerol, diglycerin, diisopropyl ether, and the like; Preferred are tetrafunctional polyols such as dimethylolpropane; pentafunctional polyols such as arabitol; hexafunctional polyols such as dulcitol, sorbitol, mannitol, dipentaerythritol, and triglycerol; cyclic dextrin; and water-soluble polyamines such as ethylenediamine, propylenediamine, 1,4-diaminobutane, hexamethylenediamine, dipropylenetriamine, tris(2-aminoethyl)amine, diethylenetriamine, triethylenetetramine, and tetraethylenepentamine.
[0089] As the component (b3), it is preferable to use polyvinyl alcohol or anion-modified polyvinyl alcohol.
[0090] In the present invention, when the fine hollow particles are formed of a resin membrane made of an amide resin, any suitable amidation catalyst can be used without any restrictions. Specific examples include boron, sodium dihydrogen phosphate, etc.
[0091] In addition, when the fine hollow particles are formed of a resin film made of a urethane (urea) resin, or when a urethane prepolymer is synthesized, any suitable urethane catalyst can be used without any restrictions. Specific examples include triethylenediamine, hexamethylenetetramine, N,N-dimethyloctylamine, N,N,N',N'-tetramethyl-1,6-diaminohexane, 4,4'-trimethylenebis(1-methylpiperidine), 1,8-diazabicyclo-(5,4,0)-7-undecene, dimethyltin dichloride, dimethyltin bis(isooctylthioglycolate), dibutyltin dichloride, dibutyltin dilaurate, dibutyltin maleate, dibutyltin maleate polymer, dibutyltin diricinoleate, dibutyltin bis(dodecyl mercaptide), dibutyltin bis(isooctyl dioctyltin dichloride, dioctyltin maleate, dioctyltin maleate polymer, dioctyltin bis(butyl maleate), dioctyltin dilaurate, dioctyltin diricinoleate, dioctyltin dioleate, dioctyltin di(6-hydroxy)caproate, dioctyltin bis(isooctylthioglycolate), didodecyltin diricinoleate, and various metal salts such as copper oleate, copper acetylacetonate, iron acetylacetonate, iron naphthenate, iron lactate, iron citrate, iron gluconate, potassium octanoate, and 2-ethylhexyl titanate.
[0092] In the present invention, in order to further stabilize the emulsion, additives may be added to the aqueous phase within a range that does not impair the effects of the present invention. Examples of such additives include water-soluble salts such as sodium carbonate, calcium carbonate, potassium carbonate, sodium phosphate, potassium phosphate, calcium phosphate, sodium chloride, and potassium chloride. These additives may be used alone or in combination of two or more.
[0093] The hollow microparticles of the present invention can be used in a variety of applications, including, for example, in many fields such as agricultural chemicals, medicines, cosmetic materials, liquid crystals, adhesives, electronic material parts, building materials, etc. In particular, the hollow microparticles of the present invention can be suitably used for applications such as shoe soles and insoles, heat insulation materials, soundproofing materials, and CMP polishing pads.
[0094] As a method for use in the above-mentioned CMP polishing pad application, any known method can be adopted without limitation. For example, a resin containing the microhollow particles of the present invention as a foaming agent can be cut and the surface polished to produce a CMP polishing pad having pores on the polished surface of the resin.
[0095] The resin is not particularly limited, but in the present invention, polyurethane resin described below is particularly suitable. In particular, the hollow microparticles of the present invention have good compatibility with polyurethane resin, so that when used in a CMP polishing pad, the hollow microparticles are less likely to fall off, and scratch resistance can be improved.
[0096] The density of the CMP polishing pad of the present invention is 0.40 to 1.10 g / cm 3 is preferably 0.50 to 1.05 g / cm 3It is more preferable that the foaming agent is a foaming agent. The foaming agent is a foaming agent that is a foaming agent that is a foaming agent that is a foaming agent that is a foaming agent. The foaming agent ...
[0097] The CMP polishing pad of the present invention can have any suitable hardness. The hardness in the present invention can be measured according to the Shore method, for example, according to JIS standard (hardness test) K6253. In the present invention, the Shore hardness of the CMP polishing pad is preferably 30A to 80D, and more preferably 40A to 70D (wherein "A" indicates hardness on the Shore "A" scale, and "D" indicates hardness on the Shore "D" scale). That is, for example, 30A to 80D means that the Shore A hardness is 30 or more and the Shore D hardness is 70 or less.
[0098] The hardness can be adjusted to any desired value by changing the blending composition and blending amount as necessary.
[0099] Furthermore, the CMP polishing pad of the present invention preferably has a compression ratio in the following range in order to achieve flatness of the polished object. The compression ratio can be measured by a method in accordance with JIS L 1096. The compression ratio is preferably 0.5% to 50%. By being within the above range, it is possible to achieve excellent flatness of the polished object.
[0100] The abrasion resistance of the CMP polishing pad of the present invention is preferably 60 mg or less, more preferably 50 mg or less, in the Taber abrasion test. By reducing the Taber abrasion amount, it becomes possible to exhibit excellent abrasion resistance when used as a CMP polishing pad.
[0101] The form of the CMP polishing pad of the present invention is not particularly limited, and for example, a groove structure may be formed on the surface. The groove structure of the CMP polishing pad is preferably a shape that retains and renews the slurry, and specific examples thereof include X (stripe) grooves, XY lattice grooves, concentric grooves, through holes, non-through holes, polygonal columns, cylinders, spiral grooves, eccentric circular grooves, radial grooves, and combinations of these grooves.
[0102] In addition, the method of making the groove structure of the CMP polishing pad is not particularly limited. For example, the method of making by pouring the above-mentioned compound into a mold having a predetermined groove structure and hardening it, or the method of making the groove structure using the obtained resin, for example, the method of mechanically cutting using a tool such as a bite of a predetermined size, the method of pressing the resin with a press plate having a predetermined surface shape, the method of making using photolithography, the method of making using a printing method, the method of making using laser light such as carbon dioxide laser, etc. can be mentioned.
[0103] The CMP polishing pad of the present invention may be composed of a plurality of layers. In this case, the cured body of the present invention may be used in at least one of the layers. For example, when the CMP polishing pad is composed of two layers, it is composed of a polishing layer (also called the first layer) having a polishing surface that contacts the workpiece during polishing, and a base layer (also called the second layer) that contacts the first layer on a surface opposite to the polishing surface of the first layer. In this case, it is possible to adjust the characteristics of the CMP polishing pad by making the second layer and the first layer have different hardnesses and elastic moduli. In this case, it is preferable that the base layer has a lower hardness than the polishing layer. In the present invention, it is preferable to use the cured body of the present invention as the polishing layer, and further, the cured body of the present invention may be used for the base layer as well.
[0104] The polyurethane resin used in the above-mentioned CMP polishing pad will be described in detail below.
[0105] The polyurethane resin in the CMP polishing pad may be prepared by a known method without any particular limitation, so long as the fine medium particles are dispersed in the polyurethane resin. For example, a method of uniformly mixing and dispersing (c) a polyfunctional isocyanate compound (hereinafter also referred to as "component (c)"), (d) a compound having active hydrogen groups capable of curing with an isocyanate group, such as two or more hydroxyl groups, thiol groups, and amino groups (hereinafter also referred to as "component (d)"), the fine hollow particles of the present invention, and other compounding components as necessary, followed by curing can be mentioned.
[0106] The curing method is not particularly limited and may be a known method, for example, the conditions described in International Publication Nos. WO2015 / 068798, WO2016 / 143910, and WO2018-092826. Specifically, dry methods such as the one-pot method and the prepolymer method, and wet methods using a solvent may be used. Among these, the dry method is preferably used.
[0107] The amount of the hollow microparticles of the present invention blended into the polyurethane resin is preferably 0.1 to 20 parts by mass, more preferably 0.2 to 10 parts by mass, and even more preferably 0.5 to 8 parts by mass, per 100 parts by mass of the total of the components (c) and (d). By adjusting the amount within this range, it is possible to exhibit excellent polishing properties.
[0108] In the present invention, the polyurethane resin is a general term for polyurethane resin, polyurea resin, and polyurethane urea resin. Furthermore, the polyurethane resin of the present invention also includes polythiourethane resin and polythiourethane resin.
[0109] Each component will be described in detail below.
[0110] <(c) Polyfunctional isocyanate compounds> In the present invention, the component (c) may be a known compound, but a urethane prepolymer having iso(thio)cyanate groups at both ends of the molecule obtained by reacting (d1) a compound having an isocyanate group and two curable active hydrogen groups in one molecule (hereinafter also referred to as "component (d1)") described later with (c1) a bifunctional iso(thio)cyanate group-containing compound having two isocyanate groups in the molecule (hereinafter also referred to as "component (c1)" or "bifunctional iso(thio)cyanate group-containing compound"). In the present invention, the iso(thio)cyanate group refers to an isocyanate group or an isothiocyanate group. Therefore, having two isocyanate groups in the molecule refers to any of the cases of having two isocyanate groups, having two isothiocyanate groups, and having one isocyanate group and one isothiocyanate group.
[0111] As the component (c), any known compound may be used without any restrictions so long as it contains an iso(thio)cyanate group at both ends of the molecule, and they may be used alone or in combination of two or more kinds.
[0112] In the present invention, examples of the component (c) or the component (c1) that is a raw material for the urethane prepolymer include polymerizable monomers described in WO 2019 / 198675.
[0113] Among these, specifically, it is preferable to use 1,5-naphthalene diisocyanate, xylylene diisocyanate (o-, m-, p-), 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, phenylene diisocyanate (o-, m-, p-), 2,2'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, isophorone diisocyanate, 1,3-bis(isocyanatemethyl)cyclohexane, dicyclohexylmethane-4,4'-diisocyanate, (bicyclo[2.2.1]heptane-2,5(2,6)-diyl)bismethylene diisocyanate, and particularly preferably aromatic isocyanates, and most preferably 2,4-tolylene diisocyanate or a urethane prepolymer made of 2,6-tolylene diisocyanate.
[0114] In order for the cured product obtained by curing the curable composition of the present invention to exhibit particularly excellent properties, it is preferable to produce the urethane prepolymer using at least one type of component (d1) having a number average molecular weight of 300 to 1,500.
[0115] The (d1) component having a number average molecular weight of 300 to 1,500 may be used in combination with different types or molecular weights, provided that the combination is such that the total number average molecular weight of the (d1) component is 300 to 1,500.
[0116] Furthermore, in order to adjust the hardness, strength, etc. of the resulting cured product, when producing the urethane prepolymer, the (d1) component having a number average molecular weight of 300 to 1,500 can be used in combination with the (d1) component having a number average molecular weight of 90 to 300. In this case, depending on the types of (d1) component and (c1) component used and their amounts used, the (d1) component having a molecular weight of 90 to 300 is preferably 0 to 50 parts by mass, more preferably 5 to 40 parts by mass, and most preferably 5 to 30 parts by mass, per 100 parts by mass of the (d1) component having a molecular weight of 300 to 1500.
[0117] In addition, the (c) component must have isocyanate and / or isothiocyanate groups at both ends of the molecule. Therefore, it is preferable to produce the (c) component in such a range that the total number of moles (n5) of isocyanate and / or isothiocyanate groups in the (c) component and the total number of moles (n6) of hydroxyl groups, thiol groups, and amino groups in the (d) component are 1<(n5) / (n6)≦2.3. When two or more kinds of (c) components are used, the number of moles (n5) of isocyanate and / or isothiocyanate groups is, of course, the total number of moles of isocyanate groups and / or isothiocyanate groups in the (c) component. In addition, the number of moles (n6) of hydroxyl groups, thiol groups, and amino groups in two or more kinds of (d1) components is, of course, the total number of moles of all hydroxyl groups, thiol groups, and amino groups.
[0118] As the (d1) component, those described in the description of the (d) component below can be used, but preferred (d1) components include polyester polyols, polyether polyols, polycarbonate polyols, etc., and among these, (d1) components consisting of polyoxytetramethylene glycol, polypropylene glycol, polyethylene glycol, diethylene glycol, etc. are most preferred.
[0119] The isocyanate equivalent of the (c) component (total amount of isocyanate equivalent and / or isothiocyanate equivalent) can be determined by quantifying the isocyanate group and / or isothiocyanate group of the (c) component in accordance with JIS K 7301. The isocyanate group and / or isothiocyanate group can be determined by the following back titration method. First, the obtained (c) component is dissolved in a dry solvent. Next, di-n-butylamine, which is clearly in excess of the amount of isocyanate group and / or isothiocyanate group of the (c) component and has a known concentration, is added to the dry solvent, and all the isocyanate group and / or isothiocyanate group of the (c) component is reacted with the di-n-butylamine. Next, the di-n-butylamine that is not consumed (not involved in the reaction) is titrated with an acid to determine the amount of di-n-butylamine consumed. Since the amount of di-n-butylamine consumed is the same as the amount of isocyanate groups and / or isothiocyanate groups in component (c), the iso(thio)cyanate equivalent can be calculated. In addition, since component (c) is a linear urethane prepolymer with isocyanate groups and / or isothiocyanate groups at both ends, the number average molecular weight of component (c) is twice the iso(thio)cyanate equivalent. This molecular weight of component (c) tends to match the value measured by gel permeation chromatography (GPC).
[0120] The iso(thio)cyanate equivalent of the (c) component is not particularly limited, but the iso(thio)cyanate equivalent in the present invention is preferably 300 to 2000, more preferably 350 to 1500, and most preferably 400 to 1000. The reason for this is considered as follows. That is, when the (c) component having a certain molecular weight is reacted with the (d) component to form a cured product, the working site of the molecule including the side chain becomes large, and the movement of the molecule itself becomes large, and as a result, it is considered that it is easy to recover (elastic recovery; low hysteresis) even against deformation. Furthermore, it is considered that by using the (c) component, the crosslinking points in the cured product are easily dispersed and exist randomly and uniformly, and stable performance is exhibited. And, the (c) component in the above-mentioned range has excellent handleability of the obtained curable composition, and it is easy to control during production, and it is possible to improve moldability. For example, when the cured product obtained by curing the curable composition of the present invention is used as a polishing pad, it is possible to produce a polishing pad with excellent moldability.
[0121] The method for producing the urethane prepolymer used in the present invention is not particularly limited, and the urethane prepolymer having an isocyanate group and / or an isothiocyanate group at the molecular terminal may be produced by reacting the component (c1) with the component (d1) using a known method.
[0122] Furthermore, the component (c) can be produced by heating or adding a urethanization catalyst as necessary.
[0123] <(d) Compounds Having an Isocyanate Group and Two or More Curable Active Hydrogen Groups> The component (d) can be any compound having at least two or more groups selected from the group consisting of hydroxyl groups, thiol groups, and amino groups in one molecule. Of course, a compound having any two or all of the hydroxyl groups, thiol groups, and amino groups can also be selected. As mentioned above, a compound having an isocyanate group and two curable active hydrogen groups in one molecule corresponds to the component (d1).
[0124] Among them, it is preferable that the (d) component contains (da) a compound having two or more amino groups (hereinafter also referred to as "(da) component") in addition to the (d1) component used to synthesize the urethane prepolymer, and more preferably contains (db) a compound having three or more hydroxyl groups and / or thiol groups (hereinafter also referred to as "(db) component"). In the present invention, a compound having n or more hydroxyl groups and / or thiol groups means that the total number of hydroxyl groups and thiol groups in the compound is n or more, and may be a compound having a hydroxyl group but not a thiol group, a compound having a thiol group but not a hydroxyl group, or a compound having both a hydroxyl group and a thiol group.
[0125] Among them, the (db) component is particularly preferably a compound having five or more hydroxyl groups and / or thiol groups, and the number of moles of hydroxyl groups and / or thiol groups per mass of the (db) component is preferably 0.5 mmol / g to 35 mmol / g, and more preferably 0.8 mmol / g to 20 mmol / g.
[0126] ((da) Compound having two or more amino groups; (da) component) The component (da) can be any compound having two or more primary and / or secondary amino groups in one molecule without any restrictions. Compounds having two or more amino groups can be broadly classified into aliphatic amines, alicyclic amines, aromatic amines, and polyrotaxanes having an amino group polymerizable with an isocyanate group.
[0127] Aliphatic amines (da) Bifunctional amines such as ethylenediamine, hexamethylenediamine, nonamethylenediamine, undecanemethylenediamine, dodecamethylenediamine, metaxylenediamine, 1,3-propanediamine, and putrescine (corresponding to the component (d1) constituting the urethane prepolymer).
[0128] Polyfunctional amines such as polyamines such as diethylenetriamine.
[0129] Alicyclic amines; (da) components Bifunctional amines such as isophoronediamine and cyclohexyldiamine (corresponding to the component (d1) constituting the urethane prepolymer).
[0130] Aromatic amines; (da) components 4,4'-methylenebis(o-chloroaniline) (MOCA), 2,6-dichloro-p-phenylenediamine, 4,4'-methylenebis(2,3-dichloroaniline), 4,4'-methylenebis(2-ethyl-6-methylaniline), 3,5-bis(methylthio)-2,4-toluenediamine, 3,5-bis(methylthio)-2,6-toluenediamine, 3,5-diethyltoluene-2,4-diamine, 3,5-diethyltoluene -2,6-diamine, trimethylene glycol-di-p-aminobenzoate, polytetramethylene glycol-di-p-aminobenzoate, 4,4'-diamino-3,3',5,5'-tetraethyldiphenylmethane, 4,4'-diamino-3,3'-diisopropyl-5,5'-dimethyldiphenylmethane, 4,4'-diamino-3,3',5,5'-tetraisopropyldiphenylmethane, 1,2-bis(2-aminophenyl) Nylthio)ethane, 4,4'-diamino-3,3'-diethyl-5,5'-dimethyldiphenylmethane, N,N'-di-sec-butyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-4,4'-diaminodiphenylmethane, m-xylylenediamine, N,N'-di-sec-butyl-p-phenylenediamine, m-phenylenediamine, p-xylylenediamine, p-phenylenediamine, 3,3'-methylenebi bifunctional amines such as 2,4-diamino-4-chlorobenzoate, 2-methylpropyl 2,4-diamino-4-chlorobenzoate, isopropyl 2,4-diamino-4-chlorophenylacetate, di-(2-aminophenyl)thioethyl terephthalate, diphenylmethanediamine, tolylenediamine, and piperazine (corresponding to the component (d1) constituting the urethane prepolymer).
[0131] Polyfunctional amines such as 1,3,5-benzenetriamine and melamine.
[0132] Polyrotaxane having amino groups; (da) component The polyrotaxane having an amino group used in the present invention is not particularly limited, and examples thereof include the polyrotaxanes described in International Application No. 2018 / 092826.
[0133] Among the components (da) used in the present invention, preferred ones include 4,4'-methylenebis(o-chloroaniline) (MOCA), 4,4'-diamino-3,3'-diethyl-5,5'-dimethyldiphenylmethane, 3,5-diethyltoluene-2,4-diamine, 3,5-diethyltoluene-2,6-diamine, 3,5-bis(methylthio)-2,4-toluenediamine, 3,5-bis(methylthio)-2,6-toluenediamine, and trimethylene glycol-di-p-aminobenzoate.
[0134] Among the components (d), compounds having a hydroxyl group and / or a thiol group can be broadly classified into aliphatic alcohols, alicyclic alcohols, aromatic alcohols, polyester polyols, polyether polyols, polycaprolactone polyols, polycarbonate polyols, polyacrylic polyols, castor oil-based polyols, thiols, monomers containing a hydroxyl group and a thiol group-type polymerizable group, side chain-containing cyclic compounds having three or more hydroxyl groups and / or thiol groups, and polyrotaxanes having a hydroxyl group and / or a thiol group. Specific examples include the following. ((d) Compound having two or more hydroxyl groups; (d) component) Fatty alcohol; (d) component Bifunctional polyols such as ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, butylene glycol, 1,5-dihydroxypentane, 1,6-dihydroxyhexane, 1,7-dihydroxyheptane, 1,8-dihydroxyoctane, 1,9-dihydroxynonane, 1,10-dihydroxydecane, 1,11-dihydroxyundecane, 1,12-dihydroxydodecane, neopentyl glycol, glyceryl monooleate, monoelaidin, polyethylene glycol, 3-methyl-1,5-dihydroxypentane, dihydroxyneopentyl, 2-ethyl-1,2-dihydroxyhexane, and 2-methyl-1,3-dihydroxypropane (corresponding to the component (d1) constituting the urethane prepolymer).
[0135] Polyfunctional polyols such as glycerin, trimethylolethane, trimethylolpropane, ditrimethylolpropane, trimethylolpropane tripolyoxyethylene ether (for example, TMP-30, TMP-60, TMP-90, etc., manufactured by Nippon Nyukazai Co., Ltd.), butanetriol, 1,2-methylglucoside, pentaerythritol, dipentaerythritol, tripentaerythritol, sorbitol, erythritol, threitol, ribitol, arabinitol, xylitol, allitol, mannitol, dolcitol, iditol, glycol, inositol, hexanetriol, triglycerol, diglycerol, and triethylene glycol (corresponding to the above-mentioned component (cb)).
[0136] Alicyclic alcohol; (d) component Hydrogenated bisphenol A, cyclobutanediol, cyclopentanediol, cyclohexanediol, cycloheptanediol, cyclooctanediol, cyclohexanedimethanol, hydroxypropylcyclohexanol, tricyclo[5,2,1,0 2,6 ]decane-dimethanol, bicyclo[4,3,0]-nonanediol, dicyclohexanediol, tricyclo[5,3,1,13,9]dodecanediol, bicyclo[4,3,0]nonane dimethanol, tricyclo[5,3,1,1 3,9]dodecane-diethanol, hydroxypropyltricyclo〔5,3,1,1 3,9 ]dodecanol, spiro[3,4]octanediol, butylcyclohexanediol, 1,1'-bicyclohexylidene diol, 1,4-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,2-cyclohexanedimethanol, and o-dihydroxyxylylene, and other bifunctional polyols (corresponding to the component (d1) constituting the urethane prepolymer).
[0137] Polyfunctional polyols such as tris(2-hydroxyethyl)isocyanurate, cyclohexanetriol, sucrose, maltitol, and lactitol (corresponding to the above-mentioned component (db)).
[0138] Aromatic alcohol; (d) component Dihydroxynaphthalene, dihydroxybenzene, bisphenol A, bisphenol F, xylylene glycol, tetrabromobisphenol A, bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 1,2-bis(4-hydroxyphenyl)ethane, bis(4-hydroxyphenyl)phenylmethane, bis(4-hydroxyphenyl)diphenylmethane, bis(4-hydroxyphenyl)-1-naphthylmethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2-(4-hydroxyphenyl) 2,2-bis(4-hydroxyphenyl)-2-(3-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 1,1-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)-3-methylbutane, 2,2-bis(4-hydroxyphenyl)pentane, 3,3-bis(4-hydroxyphenyl)pentane, 2,2-bis(4-hydroxyphenyl)hexane, 2,2-bis(4-hydroxyphenyl)octane, 2,2-bis(4-hydroxyphenyl)-4-methylpentane, 2,2-bis(4-hydroxyphenyl)hexane butane, 4,4-bis(4-hydroxyphenyl)heptane, 2,2-bis(4-hydroxyphenyl)tridecane, 2,2-bis(4-hydroxyphenyl)octane, 2,2-bis(3-methyl-4-hydroxyphenyl)propane, 2,2-bis(3-ethyl-4-hydroxyphenyl)propane, 2,2-bis(3-n-propyl-4-hydroxyphenyl)propane, 2,2-bis(3-isopropyl-4-hydroxyphenyl)propane, 2,2-bis(3-sec-butyl-4-hydroxyphenyl)propane, 2,2-bis(3- tert-butyl-4-hydroxyphenyl)propane, 2,2-bis(3-cyclohexyl-4-hydroxyphenyl)propane, 2,2-bis(3-allyl-4'-hydroxyphenyl)propane, 2,2-bis(3-methoxy-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 2,2-bis(2,3,5,6-tetramethyl-4-hydroxyphenyl)propane, bis(4-hydroxyphenyl)cyanomethane, 1-cyano-3,3-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)hexafluoropropane, 1,1-bis(4-hydroxyphenyl)cyclopentane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)cycloheptane, 1,1-bis(3-methyl-4-hydroxyphenyl)cyclohexane, 1,1-bis(3,5-dimethyl-4-hydroxyphenyl)cyclohexane, 1,1-bis(3,5-dichloro-4-hydroxyphenyl)cyclohexane, 1,1-bis(3-methyl-4-hydroxyphenyl)-4-methylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 2,2-bis(4-hydroxyphenyl)norbornane, 2,2-bis(4-hydroxyphenyl)adamantane, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dimethyldiphenyl ether, ethylene glycol bis(4-hydroxyphenyl)ether, 4,4'- Dihydroxydiphenyl sulfide, 3,3'-dimethyl-4,4'-dihydroxydiphenyl sulfide, 3,3'-dicyclohexyl-4,4'-dihydroxydiphenyl sulfide, 3,3'-diphenyl-4,4'-dihydroxydiphenyl sulfide, 4,4'-dihydroxydiphenyl sulfoxide, 3,3'-dimethyl-4,4'-dihydroxydiphenyl sulfoxide, 4,4'-dihydroxydiphenyl sulfone, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfone, bis(4-hydroxyphenyl) ketone, bis(4-hydroxy-3-methylphenyl) ketone, 7,7' -Dihydroxy-3,3',4,4'-tetrahydro-4,4,4',4'-tetramethyl-2,2'-spirobi(2H-1-benzopyran), trans-2,3-bis(4-hydroxyphenyl)-2-butene, 9,9-bis(4-hydroxyphenyl)fluorene, 3,3-bis(4-hydroxyphenyl)-2-butanone, 1,6-bis(4-hydroxyphenyl)-1,6-hexanedione, 4,4'-dihydroxybiphenyl, m-dihydroxyxylylene, p-dihydroxyxylylene, 1,4-bis(2-hydroxyethyl)benzene, 1,4-bis(3-hydroxypropyl)benzene, 1,4-bis(4-hydroxybutyl)benzene, 1,4-bis(5-hydroxypentyl)benzene, 1,4-bis(6-hydroxyhexyl)benzene, 2,2-bis[4-(2''-hydroxyethyloxy)phenyl]propane, and bifunctional polyols such as hydroquinone and resorcinol (corresponding to the component (d1) constituting the urethane prepolymer).
[0139] Polyfunctional polyols such as trihydroxynaphthalene, tetrahydroxynaphthalene, benzenetriol, biphenyltetraol, pyrogallol, (hydroxynaphthyl)pyrogallol, and trihydroxyphenanthrene (corresponding to the above-mentioned component (db)).
[0140] Polyester polyol; component (d) Examples of such compounds include compounds obtained by a condensation reaction between a polyol and a compound having multiple carboxylic acids. Among these, the number average molecular weight is preferably 400 to 2000, more preferably 500 to 1500, and most preferably 600 to 1200. Note that those having hydroxyl groups only at both ends of the molecule (two in the molecule) correspond to the component (d1) constituting the urethane prepolymer, and those having three or more hydroxyl groups in the molecule correspond to the component (db).
[0141] Here, examples of the polyol include ethylene glycol, 1,2-propanediol, 1,3-butanediol, 1,4-butanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 3,3'-dimethylolheptane, 1,4-cyclohexanedimethanol, neopentyl glycol, 3,3-bis(hydroxymethyl)heptane, diethylene glycol, dipropylene glycol, glycerin, and trimethylolpropane, which may be used alone or in combination of two or more. Examples of the compound having multiple carboxylic acids include succinic acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, cyclopentanedicarboxylic acid, cyclohexanedicarboxylic acid, orthophthalic acid, isophthalic acid, terephthalic acid, and naphthalenedicarboxylic acid, which may be used alone or in combination of two or more.
[0142] These polyester polyols are available as reagents or industrially, and examples of commercially available products include the "Polylite (registered trademark)" series manufactured by DIC Corporation, the "Nipporun (registered trademark)" series manufactured by Nippon Polyurethane Industry Co., Ltd., the "Maximol (registered trademark)" series manufactured by Kawasaki Chemical Industries, Ltd., and the "Kuraray Polyol (registered trademark)" series manufactured by Kuraray Co., Ltd.
[0143] Polyether polyol; component (d) Examples of such compounds include compounds obtained by ring-opening polymerization of alkylene oxides, or by the reaction of a compound having two or more active hydrogen groups in the molecule with an alkylene oxide, and modified compounds thereof. Among these, the number average molecular weight is preferably 400 to 2000, more preferably 500 to 1500, and most preferably 600 to 1200. Note that those having hydroxyl groups only at both ends of the molecule (two in the molecule) correspond to the component (d1) constituting the urethane prepolymer, and those having three or more hydroxyl groups in the molecule correspond to the component (db).
[0144] Examples of the polyether polyol include polymer polyol, urethane-modified polyether polyol, polyether ester copolymer polyol, etc., and examples of the compound having two or more active hydrogen groups in the molecule include polyol compounds such as water, ethylene glycol, propylene glycol, butanediol, glycerin, trimethylolpropane, hexanetriol, triethanolamine, diglycerin, pentaerythritol, trimethylolpropane, hexanetriol, etc., which have one or more hydroxyl groups in the molecule, and glycerin, and these may be used alone or in combination of two or more.
[0145] Examples of the alkylene oxide include cyclic ether compounds such as ethylene oxide, propylene oxide, and tetrahydrofuran. These may be used alone or in combination of two or more kinds.
[0146] Such polyether polyols are available as reagents or industrially, and examples of commercially available polyether polyols include the "EXCENOL (registered trademark)" series and "EMULSTAR (registered trademark)" manufactured by Asahi Glass Co., Ltd., and the "ADEKA POLYETHER" series manufactured by ADEKA Corporation.
[0147] Polycaprolactone polyol; component (d) Examples of such compounds include compounds obtained by ring-opening polymerization of ε-caprolactone. Among these, the number average molecular weight is preferably 400 to 2000, more preferably 500 to 1500, and most preferably 600 to 1200. Note that compounds having hydroxyl groups only at both ends of the molecule (two hydroxyl groups in the molecule) correspond to the component (d1) constituting the urethane prepolymer, and compounds having three or more hydroxyl groups in the molecule correspond to the component (db).
[0148] These polycaprolactone polyols are available as reagents or industrially, and examples of commercially available polycaprolactone polyols include the "Placcel (registered trademark)" series manufactured by Daicel Chemical Industries, Ltd.
[0149] Polycarbonate polyol; component (d) Examples of such compounds include compounds obtained by phosgenating one or more low molecular weight polyols, and compounds obtained by transesterification using ethylene carbonate, diethyl carbonate, diphenyl carbonate, etc. Among these, the number average molecular weight is preferably 400 to 2000, more preferably 500 to 1500, and most preferably 600 to 1200. Note that those having hydroxyl groups only at both ends of the molecule (two hydroxyl groups in the molecule) correspond to the component (d1) constituting the urethane prepolymer, and those having three or more hydroxyl groups in the molecule correspond to the component (cd).
[0150] Examples of the low molecular weight polyol include low molecular weight polyols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 2-methyl-1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 3-methyl-1,5-pentanediol, 2-ethyl-4-butyl-1,3-propanediol, diethylene glycol, dipropylene glycol, neopentyl glycol, cyclohexane-1,4-diol, cyclohexane-1,4-dimethanol, diol dimer acid, ethylene oxide or propylene oxide adduct of bisphenol A, bis(β-hydroxyethyl)benzene, xylylene glycol, glycerin, trimethylolpropane, and pentaerythritol.
[0151] Polyacrylic polyol; component (d) Examples of the polyol compound include those obtained by polymerizing (meth)acrylate esters and vinyl monomers. Note that those having hydroxyl groups only at both ends of the molecule (two in the molecule) correspond to the component (d1) constituting the urethane prepolymer, and those having three or more hydroxyl groups in the molecule correspond to the component (db).
[0152] Castor oil-based polyol; component (d) Castor oil-based polyols include polyol compounds that use castor oil, a natural fat, as a starting material. Note that those that have hydroxyl groups only at both ends of the molecule (two in the molecule) correspond to the (d1) component constituting the urethane prepolymer, and those that have three or more hydroxyl groups in the molecule correspond to the (db) component.
[0153] These castor oil polyols are available as reagents or industrially, and examples of commercially available products include the "URIC (registered trademark)" series manufactured by Ito Oil Mills, Ltd.
[0154] ((d) Compounds Having Two or More Thiol Groups) Among the (d) components, specific examples of suitable compounds having a thiol group include those described in International Publication No. WO2015 / 068798. Among these, particularly suitable examples include the following:
[0155] Tetraethylene glycol bis(3-mercaptopropionate), 1,4-butanediol bis(3-mercaptopropionate), 1,6-hexanediol bis(3-mercaptopropionate), 1,4-bis(mercaptopropylthiomethyl)benzene (corresponding to the component (d1) constituting the urethane prepolymer).
[0156] Trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptopropionate), dipentaerythritol hexakis(3-mercaptopropionate), 1,2-bis[(2-mercaptoethyl)thio]-3-mercaptopropane, 2,2-bis(mercaptomethyl)-1,4-butanedithiol, 2,5-bis(mercaptomethyl)-1,4-dithiane, 4-mercaptomethyl thiols (corresponding to the above-mentioned component (db)), such as 1,8-dimercapto-3,6-dithiaoctane, 1,1,1,1-tetrakis(mercaptomethyl)methane, 1,1,3,3-tetrakis(mercaptomethylthio)propane, 1,1,2,2-tetrakis(mercaptomethylthio)ethane, 4,6-bis(mercaptomethylthio)-1,3-dithiane, and tris-{(3-mercaptopropionyloxy)ethyl}-isocyanurate.
[0157] (d) Hydroxyl- and Thiol-Polymerizable Group-Containing Monomers Among the components (d), examples of compounds having both a hydroxyl group and a thiol group include the following.
[0158] 2-mercaptoethanol, 1-hydroxy-4-mercaptocyclohexane, 2-mercaptohydroquinone, 4-mercaptophenol, 1-hydroxyethylthio-3-mercaptoethylthiobenzene, 4-hydroxy-4'-mercaptodiphenyl sulfone, 2-(2-mercaptoethylthio)ethanol, dihydroxyethyl sulfide mono(3-mercaptopropionate), dimercaptoethane mono(saltyrate) (corresponding to the component (d1) constituting the urethane prepolymer).
[0159] Polyfunctional OH / SH type polymerizable group-containing monomers (corresponding to the above-mentioned (db) component) such as 3-mercapto-1,2-propanediol, glycerin di(mercaptoacetate), 2,4-dimercaptophenol, 1,3-dimercapto-2-propanol, 2,3-dimercapto-1-propanol, 1,2-dimercapto-1,3-butanediol, pentaerythritol tris(3-mercaptopropionate), pentaerythritol mono(3-mercaptopropionate), pentaerythritol bis(3-mercaptopropionate), pentaerythritol tris(thioglycolate), pentaerythritol pentakis(3-mercaptopropionate), hydroxymethyl-tris(mercaptoethylthiomethyl)methane, and hydroxyethylthiomethyltris(mercaptoethylthio)methane.
[0160] A side chain-containing cyclic molecule having three or more hydroxyl groups and / or thiol groups; (db) component In the present invention, the cyclic molecule is not particularly limited as long as it contains a side chain having three or more hydroxyl groups and / or thiol groups at the end. For example, examples of the cyclic molecule that serves as the base include cyclodextrin, crown ether, benzocrown, dibenzocrown, dicyclohexanocrown, cyclobis(paraquat-1,4-phenylene), dimethoxypillararenes, calixarenes, and phenanthrolines, and among these, cyclodextrin is preferred.
[0161] The cyclodextrin includes α-cyclodextrin (inner ring diameter 0.45 to 0.6 nm), β-cyclodextrin (inner ring diameter 0.6 to 0.8 nm), and γ-cyclodextrin (inner ring diameter 0.8 to 0.95 nm). Mixtures of these may also be used. In the present invention, α-cyclodextrin and β-cyclodextrin are particularly preferred.
[0162] Next, the side chains having a hydroxyl group and / or a thiol group at the end, which are introduced into the cyclic molecule in at least three units, will be described. The method for introducing the side chains is not limited, but for example, the side chains can be introduced by utilizing a reactive functional group possessed by the cyclic molecule and modifying this reactive functional group (i.e., the side chains are introduced by reacting with the reactive functional group).
[0163] Examples of the reactive functional group include a hydroxyl group and an amino group, and among these, a hydroxyl group is preferred. For example, α-cyclodextrin has 18 hydroxyl groups as reactive functional groups, and side chains are introduced by reacting with these hydroxyl groups. Therefore, a maximum of 18 side chains can be introduced into one α-cyclodextrin. In the present invention, in order to fully exert the function of the side chains described above, at least three or more side chains having hydroxyl groups and / or thiol groups introduced at the terminals must be introduced. Among them, it is preferable that five or more side chains having hydroxyl groups and / or thiol groups are introduced at the terminals, more preferably seven or more side chains having hydroxyl groups and / or thiol groups are introduced at the terminals, and most preferably eight or more side chains having hydroxyl groups and / or thiol groups are introduced at the terminals. In addition, side chains having a hydroxyl group at the terminal are particularly preferred.
[0164] The side chain is not particularly limited, but is preferably formed by repeating an organic chain having a carbon number in the range of 3 to 20. The number average molecular weight of such a side chain is preferably, for example, 300 or more. More specifically, the number average molecular weight of such a side chain is in the range of 300 to 10,000, preferably 350 to 5,000, and most preferably 400 to 5,000. The number average molecular weight of this side chain can be adjusted by the amount used when introducing the side chain, and can be determined by calculation. 1 It can also be determined by H-NMR measurement.
[0165] By setting the lower limit of the number average molecular weight of the side chain within the above range, excellent mechanical properties are exhibited, and when used in the CMP polishing pad of the present invention, the removal rate tends to be improved.
[0166] In the present invention, the side chain may be linear or branched. The introduction of the side chain can be appropriately carried out by using the methods and compounds disclosed in International Publication No. 2015 / 159875. For example, ring-opening polymerization, radical polymerization, cationic polymerization, anionic polymerization, living radical polymerization such as atom transfer radical polymerization, RAFT polymerization, and NMP polymerization can be used. By using the above method, a side chain of an appropriate size can be introduced by reacting an appropriately selected compound with the reactive functional group of the cyclic molecule.
[0167] Among these, ring-opening polymerization is particularly preferred, and it is suitable to introduce a side chain derived from a cyclic compound such as a cyclic ether, a cyclic lactone, a cyclic acetal, or a cyclic carbonate.
[0168] Among the cyclic compounds, it is preferable to use cyclic ethers, cyclic lactones, and cyclic carbonates from the viewpoints of high reactivity and ease of molecular weight adjustment.
[0169] Examples of cyclic ethers, cyclic lactones, and cyclic carbonates that can be suitably used are given below.
[0170] Cyclic ethers; Ethylene oxide, 1,2-propylene oxide, epichlorohydrin, epibromohydrin, 1,2-butylene oxide, 2,3-butylene oxide, isobutylene oxide, oxetane, 3-methyloxetane, 3,3-dimethyloxetane, tetrahydrofuran, 2-methyltetrahydrofuran, 3-methyltetrahydrofuran, etc. Cyclic lactones; 4-membered ring lactones; β-propiolactone, β-methylpropiolactone, L-serine-β-lactone, etc. Five-membered ring lactones; γ-butyrolactone, γ-hexanolactone, γ-heptanolactone, γ-octanolactone, γ-decanolactone, γ-dodecanolactone, α-hexyl-γ-butyrolactone, α-heptyl-γ-butyrolactone, α-hydroxy-γ-butyrolactone, γ-methyl-γ-decanolactone, α-methylene-γ-butyrolactone, α,α-dimethyl-γ-butyrolactone, D-erythronolactone, α-methyl γ-butyrolactone, γ-nonanolactone, DL-pantolactone, γ-phenyl-γ-butyrolactone, γ-undecanolactone, γ-valerolactone, 2,2-pentamethylene-1,3-dioxolan-4-one, α-bromo-γ-butyrolactone, γ-crotonolactone, α-methylene-γ-butyrolactone, α-methacryloyloxy-γ-butyrolactone, β-methacryloyloxy-γ-butyrolactone, etc. 6-membered ring lactones; δ-valerolactone, δ-hexanolactone, δ-octanolactone, δ-nonanolactone, δ-decanolactone, δ-undecanolactone, δ-dodecanolactone, δ-tridecanolactone, δ-tetradecanolactone, DL-mevalonolactone, 4-hydroxy-1-cyclohexanecarboxylic acid δ-lactone, monomethyl-δ-valerolactone, monoethyl-δ-valerolactone, monohexyl-δ-valerolactone, 1,4-dioxan-2-one, 1,5-dioxepan-2-one, etc. 7-membered ring lactones; ε-caprolactone, monomethyl-ε-caprolactone, monoethyl-ε-caprolactone, monohexyl-ε-caprolactone, dimethyl-ε-caprolactone, di-n-propyl-ε-caprolactone, di-n-hexyl-ε-caprolactone, trimethyl-ε-caprolactone, triethyl-ε-caprolactone, tri-n-ε-caprolactone, ε-caprolactone, 5-nonyl-oxepan-2-one, 4,4,6-trimethyl-oxepan-2-one, 4,6,6-trimethyl-oxepan-2-one, 5-hydroxymethyl-oxepan-2-one, etc. 8-membered lactones; ζ-enantholactone, etc. Other lactones; lactone, lactide, dilactide, tetramethylglycoside, 1,5-dioxepan-2-one, t-butylcaprolactone, etc. Cyclic carbonates; Ethylene carbonate, propylene carbonate, 1,2-butylene carbonate, glycerol 1,2-carbonate, 4-(methoxymethyl)-1,3-dioxolan-2-one, (chloromethyl)ethylene carbonate, vinylene carbonate, 4,5-dimethyl-1,3-dioxol-2-one, 4-chloromethyl-5-methyl-1,3-dioxol-2-one, 4-vinyl-1,3-dioxolan-2-one, 4,5-diphenyl-1,3-dioxolan-2-one, 4,4-dimethyl-5-methylene-1,3-dioxolan-2-one, 1,3-dioxan-2-one, 5-methyl-5-propyl-1,3-dioxolan-2-one, 5,5-diethyl-1,3-dioxolan-2-one The above cyclic compounds can be used alone or in combination of two or more kinds.
[0171] In the present invention, the cyclic compound preferably used is a lactone compound, and particularly preferred lactone compounds are lactone compounds such as ε-caprolactone, α-acetyl-γ-butyrolactone, α-methyl-γ-butyrolactone, γ-valerolactone, and γ-butyrolactone, and most preferred is ε-caprolactone.
[0172] In addition, when introducing a side chain by reacting a cyclic compound by ring-opening polymerization, the reactive functional group (e.g., hydroxyl group) of the cyclic molecule may have poor reactivity, and it may be difficult to directly react a large molecule, especially due to steric hindrance. In such a case, for example, in order to react with the above-mentioned caprolactone, a method is preferable in which a low molecular weight compound such as propylene oxide is reacted with the reactive functional group of the cyclic molecule to perform hydroxypropylation, and a highly reactive functional group is introduced in advance. Then, a means can be adopted in which a side chain is introduced by ring-opening polymerization using the above-mentioned cyclic compound. In this case, the hydroxypropylated portion can also be considered as a side chain.
[0173] Polyrotaxane having a hydroxyl group and / or a thiol group; component (d) A polyrotaxane is a molecular complex having a structure in which a chain-like axial molecule penetrates the rings of multiple cyclic molecules, and bulky groups are bonded to both ends of the axial molecule, preventing the cyclic molecules from coming off the axial molecule due to steric hindrance, and is also called a supramolecule. The polyrotaxane that can be used in the component (d) of the present invention is a polyrotaxane having a hydroxyl group and / or a thiol group that can polymerize with an isocyanate group, and one having three or more hydroxyl groups and / or thiol groups corresponds to the component (db). The polyrotaxane having a hydroxyl group and / or a thiol group used in the component (d) of the present invention is not particularly limited, but for example, the polyrotaxane described in International Application Publication No. 2018 / 092826 is exemplified.
[0174] Among the (cb) components used in the present invention, preferred are glycerin, trimethylolethane, trimethylolpropane, ditrimethylolpropane, trimethylolpropane tripolyoxyethylene ether (TMP-30 from Nippon Nyukazai Co., Ltd.), polyester polyols having three or more hydroxyl groups, polyether polyols having three or more hydroxyl groups, castor oil-based polyols having three or more hydroxyl groups, side chain-containing cyclic compounds having three or more hydroxyl groups, and polyrotaxanes having hydroxyl groups and / or thiol groups, of which side chain-containing cyclic compounds having three or more hydroxyl groups and polyrotaxanes having three or more hydroxyl groups and / or thiol groups are more preferred, and from the viewpoint of handleability, side chain-containing cyclic compounds having three or more hydroxyl groups and / or thiol groups are most preferred.
[0175] <Combination ratio of components (c) and (d)> In the present invention, the blending ratio of the (c) component and the (d) component is not particularly limited. In particular, in order to exhibit excellent effects, it is preferable that the total number of moles of the active hydrogen groups of the (d) component is 0.8 to 2.0 moles when the total number of iso(thio)cyanate groups of the (c) component is 1 mole. If the iso(thio)cyanate groups are too many or too few, the resulting polyurethane resin is likely to be cured poorly or have reduced abrasion resistance. In order to obtain a polyurethane resin that is cured in a better and more uniform state and has excellent abrasion resistance, it is more preferable that the total number of moles of the active hydrogen groups is 0.85 to 1.75 moles, and even more preferable that it is 0.9 to 1.5 moles, when the total number of iso(thio)cyanate groups is 1 mole. In addition, when calculating the total number of moles of the active hydrogen groups of the (d) component, when a compound having two or more amino groups (ca) is used, the number of moles of active hydrogen of the compound having two or more amino groups is equal to the number of moles of the amino groups.
[0176] In the present invention, in order to exhibit excellent polishing properties, as described above, the component (d) preferably contains the component (da), and more preferably contains the components (da) and (db).
[0177] That is, in the present invention, it is preferable to contain the components (c) and (da), and it is more preferable to contain the components (c), (da), and (db).
[0178] For example, when the (c), (da), and (db) components are contained, the respective blending ratios are preferably 60 to 95 parts by mass of the (c), (da) and (db) components, 2 to 20 parts by mass of the (da) component, and 1 to 30 parts by mass of the (db) component, per 100 parts by mass of the combined total of the (c), (da), and (db) components, and more preferably 70 to 85 parts by mass of the (c), (da) component, and 3 to 25 parts by mass of the (db) component.
[0179] <Other ingredients> As other compounding components used in the present invention, various known compounding agents can be used within the scope of not impairing the effects of the present invention. For example, curing catalysts, abrasive grains, surfactants, flame retardants, plasticizers, fillers, antistatic agents, foam stabilizers, solvents, leveling agents, and other additives may be added. These additives may be used alone or in combination of two or more.
[0180] As the curing catalyst, the urethane or urea reaction catalyst can be any catalyst that can be used when the hollow fine particles are a urethane (urea) resin. One type can be used alone, or two or more types can be used in combination. The amount used can be a so-called catalytic amount, for example, in the range of 0.001 to 10 parts by mass, particularly 0.01 to 5 parts by mass, per 100 parts by mass of the total of the components (c) and (d).
[0181] Furthermore, examples of the abrasive grains include particles made of a material selected from cerium oxide, silicon oxide, alumina, silicon carbide, zirconia, iron oxide, manganese dioxide, titanium oxide and diamond, or particles made of two or more of these materials. EXAMPLES
[0182] Next, the present invention will be described in detail using examples and comparative examples, but the present invention is not limited to these examples. The components and evaluation methods used in the following examples and comparative examples are as follows.
[0183] (micro hollow particles) [Measurement method] (1) Average particle size, yield The electron micrographs of the obtained hollow microparticles were measured using a field emission scanning electron microscope (JSM-7800FPrime, manufactured by JEOL Ltd.), and the particle diameters of at least 50 or more individual hollow microparticles were measured using image analysis software ImageJ (National Institutes of Health), and the average particle diameter was calculated as the average of these. The yield was determined by checking the shapes of at least 50 hollow microparticles, and the percentage of hollow microparticles that were neither dented nor broken was determined as the yield.
[0184] (2) Ash content This is the ratio of the mass of the combustion residue when hollow microballoons are burned at a temperature of 600°C to the mass of the hollow microparticles before combustion.
[0185] <Example 1> As the aqueous phase, 55 ml of 2% sodium hydroxide solution was heated to 70° C. while dissolving 3.5 g of styrene-maleic anhydride copolymer (Scripset 520 (Monsanto, weight average molecular weight 350,000)) as a surfactant, and then 35 g of chlorobenzene was added to the aqueous phase as an oil phase, and the mixture was stirred at 1500 rpm for 10 minutes at 80° C. with a homogenizer to prepare an O / W emulsion. In addition, 4.54 g of melamine, 11.69 ml of 37% aqueous formaldehyde solution, and 7.12 g of distilled water were mixed at 70° C., and then pH was adjusted using 5 ml of 10% aqueous sodium hydroxide solution to cause an addition reaction of formaldehyde with melamine. Next, an alkaline aqueous solution of melamine formaldehyde prepolymer compound at 70° C. and pH 12 was prepared, and the entire amount was added to the O / W emulsion obtained above and mixed. After that, a 10% citric acid solution was added to confirm that the pH was 4 or less, and the mixture was stirred and mixed at 150 rpm while reacting at a liquid temperature of 80°C for 4 hours to generate fine particles. The obtained fine particles were then put into a centrifugal filter, centrifuged 5 times at 1000 rpm for 5 minutes to remove the water tank, and a solid was obtained. The obtained solid was made into a slurry in 100 g of ethanol, filtered through a filter paper with a mesh size of 1 μm, and then placed in a high-pressure vessel, and liquefied carbon dioxide at 16 MPa was heated to 40°C inside the device, and extraction was performed using supercritical carbon dioxide at 40 mL / min for 45 minutes. After that, the pressure was reduced to atmospheric pressure over 15 minutes to obtain fine hollow particles. It was confirmed that chlorobenzene had been removed from the obtained fine hollow particles by TG measurement. The average particle size was 23 μm. The appearance of the obtained fine hollow particles was good, and the bulk density of the obtained fine hollow particles was 0.1 g / cm 3 The yield was 90%, and the ash content was not measured. Table 1 shows the blend amounts used, the treatment conditions using supercritical fluids, and the results.
[0186] <Example 2> In Example 1, instead of forming a slurry of the solid obtained after centrifugation in 100 g of ethanol, filtering through a filter paper with a mesh size of 1 μm and placing the slurry in a high-pressure vessel, the solid obtained after centrifugation was formed into a slurry in 100 g of TBA, freeze-dried for degassing, and then placed in a high-pressure vessel. The same conditions as in Example 1 were used, except that the procedure was changed. It was confirmed by TG measurement that chlorobenzene had been removed from the obtained hollow microparticles, and the average particle size was 22 μm. The appearance of the obtained hollow microparticles was good, and the bulk density of the obtained hollow microparticles was 0.1 g / cm. 3 The yield was 90%, and the ash content was not measured. Table 1 shows the blend amounts used, the treatment conditions using supercritical fluids, and the results.
[0187] <Examples 3 to 6> Hollow microparticles were produced and evaluated in the same manner as in Example 1 or Example 2, except that the blending amounts and supercritical carbon dioxide conditions shown in Table 1 were used. The results are shown in Table 1. The resulting hollow microparticles all had a bulk density of 0.1 g / cm. 3 The yield was 90% and no ash was measured.
[0188] [Table 1]
[0189] <Comparative Example 1> Using the blending amounts shown in Table 1, the same method as in Example 1 was used to obtain a solid by centrifugation, and the obtained solid was dried in an oven at 140°C for 48 hours to obtain hollow microparticles. It was confirmed by TG measurement that chlorobenzene had been removed from the obtained hollow microparticles. The average particle size was 19.5 μm. Many of the obtained hollow microparticles had a broken appearance, and the bulk density of the obtained hollow microparticles was 0.15 g / cm. 3 The yield was 30% and the ash content was not measured. The results are shown in Table 1.
[0190] (CMP polishing pad) (c) Component Pre-1: A urethane prepolymer with an iso(thio)cyanate equivalent of 460 and iso(thio)cyanate groups at both ends. (Pre-1 manufacturing method) In a flask equipped with a nitrogen inlet tube, a thermometer, and a stirrer, 1000 g of 2,4-tolylene diisocyanate and 1100 g of polypropylene glycol (number average molecular weight; 500) were reacted at 80°C for 4 hours under a nitrogen atmosphere, and then 120 g of diethylene glycol was added and reacted at 80°C for 5 hours to obtain a terminal isocyanate urethane prepolymer (Pre-1) with an iso(thio)cyanate equivalent of 460.
[0191] (d) Ingredients ·DB-1: A cyclic compound with nine hydroxyl groups at the end of the side chain; (db) component (DB-1 manufacturing method) 10g of hydroxypropylated β-cyclodextrin (CycloChem Co., Ltd.) and 32.0g of ε-caprolactone were stirred at 130°C while flowing dry nitrogen to make a homogeneous solution, and then 0.04g of tin(II) 2-ethylhexanoate was added and reacted for 16 hours to obtain the target product, A-7. The physical properties of CB-1 were as follows: Weight average molecular weight Mw (GPC): 4800 Dispersion degree (GPC): 1.05 Side chain modification degree: 0.43 (expressed as a percentage, it is 43%) Polymerizable group at the end of the side chain: Hydroxyl group Number of side chains introduced into the cyclic molecule: 9 Side chain molecular weight: Average of about 550 Viscosity: 3,800mPa·s
[0192] [Measurement method] (3) Resin density: Density (g / cm) measured using Toyo Seiki's DSG-1 3 ) was measured.
[0193] (4)Shore D hardness: The Shore D hardness was measured using a durometer manufactured by Kobunshi Keiki Co., Ltd. in accordance with JIS standard (hardness test) K6253. The samples were piled up to a thickness of 6 mm and measured. The samples with relatively low hardness were measured using Shore A hardness, and the samples with relatively high hardness were measured using Shore D hardness.
[0194] (5) Hysteresis loss: A resin punched into a No. 8 dumbbell shape with a thickness of 2 mm was stretched by 20 mm at 10 mm / min using a Shimadzu AG-SX autograph, and then the hysteresis loss was measured when the resin was returned to its original stress state of zero.
[0195] (6) Polishing rate: The polishing rate was measured under the following conditions. The polishing rate is the average value for six 2-inch sapphire wafers.
[0196] CMP polishing pad: A pad with a diameter of 300 mm and a thickness of 1 mm, with concentric grooves formed on the surface. Slurry: FUJIMI Compol 80 concentrate Pressure: 3.0psi Rotation speed: 45 rpm Time: 1 hour
[0197] (7) Scratches: The presence or absence of scratches on the wafer when polished under the conditions described in (6) above was confirmed. The evaluation was performed according to the following criteria. 1: All six pieces are free of scratches when viewed under a laser microscope 2: Only one sheet has a thin scratch visible under a laser microscope 3: Only one sheet has a scratch that can be clearly seen with a laser microscope 4: Two or more pieces with visible scratches using a laser microscope
[0198] <Example 7> 21 parts by mass of DB-1, the component (db) prepared above, and 9 parts by mass of 4,4'-methylenebis(o-chloroaniline) (MOCA), the component (da), were mixed at 120°C to form a homogeneous solution, which was then thoroughly degassed to prepare liquid A. Separately, 70 parts by mass of Pre-1, the component (c) prepared above, which had been heated to 70°C, was added with 4.5 parts by mass of the microhollow particles of Example 1, and the mixture was stirred with a planetary centrifugal mixer to prepare liquid B, which was a homogeneous solution. Liquid A was added to the liquid B prepared above, and the mixture was mixed homogeneously to prepare a curable composition. The curable composition was poured into a mold, degassed for 2 minutes under reduced pressure of 5 kPa, and then cured at 100°C for 15 hours. After curing, the mixture was removed from the mold to obtain a cured body. The amounts of each compound are shown in Table 1.
[0199] Next, the obtained hardened body was sliced to prepare a hardened body having a thickness of 1 mm, and the following various physical properties were measured. The density of the obtained hardened body was 0.95 g / cm 3 , Shore D hardness was 48D, and hysteresis loss was 60%.
[0200] In addition, a spiral groove was formed on the surface of the 1 mm thick hardened body obtained by slicing, and double-sided tape was attached to the back side to create a polishing pad made of the hardened body with a size of 300 mmφ and a thickness of 1 mm.
[0201] The polishing rate of the polishing pad made of the cured product obtained above was 3.0 μm / hr, and the number of scratches was 2. The results are shown in Table 2.
[0202] <Comparative Example 2> A hardened body was produced in the same manner as in Example 7, except that 4.5 parts by mass of the hollow microparticles of Comparative Example 1 were used instead of the hollow microparticles of Example 1. The density of the obtained hardened body was 1.10 g / cm. 3 , Shore D hardness was 50D, and hysteresis loss was 62%.
[0203] The polishing rate of the polishing pad prepared in the same manner as in Example 1 was 1.5 μm / hr, and the number of scratches was 2. The results are shown in Table 2.
[0204] <Comparative Example 3> A hardened body was produced in the same manner as in Example 7, except that 0.8 parts by mass of commercially available Microcapsule 920-40 (manufactured by Nippon Phillite Co., Ltd., hollow microballoons made of acrylonitrile resin with inorganic powder on the surface) was used instead of the microhollow particles used in Example 1. The density of the obtained hardened body was 0.85 g / cm. 3 , Shore D hardness was 44D, and hysteresis loss was 69%.
[0205] The polishing rate of the polishing pad prepared in the same manner as in Example 1 was 1.9 μm / hr, and the number of scratches was 2. The results are shown in Table 2.
[0206] [Table 2]
Claims
1. The hollow microparticles are made of at least one resin selected from the group consisting of melamine resins, urea resins, amide resins, and urethane (urea) resins, and are obtained by preparing a water-in-oil (O / W) emulsion in which an organic solvent is the dispersed phase and an aqueous solution is the continuous phase, obtaining microparticles in which the organic solvent is encapsulated inside the microparticles, and then removing the organic solvent from the inside of the microparticles using a supercritical liquid.
2. 2. The hollow microparticles according to claim 1, wherein the supercritical liquid is supercritical carbon dioxide.
3. 3. The hollow microparticles according to claim 1, wherein the hollow microparticles are made of a melamine resin.
4. A cured product comprising the hollow microparticles according to any one of claims 1 to 3 dispersed in a polyurethane resin.
5. A CMP polishing pad comprising the cured product according to claim 4.
6. A method for producing hollow microparticles composed of a resin film made of at least one resin selected from the group consisting of melamine resins, urea resins, amide resins, and urethane (urea) resins, comprising the steps of: preparing a water-in-oil (O / W) emulsion in which an oil phase containing an organic solvent is the dispersed phase and an aqueous phase is the continuous phase; obtaining microparticles in which the organic solvent is encapsulated inside the microparticles; and then removing the organic solvent from the inside of the microparticles using a supercritical liquid.
7. A method for producing hollow microparticles composed of a resin film made of a melamine-based resin, comprising: a first step: (a) a step of preparing an oil phase containing an organic solvent; a second step: (b) a step of preparing an aqueous phase containing a surfactant made of at least one type of maleic anhydride copolymer; a third step: a step of mixing and stirring the oil phase and the aqueous phase to prepare a water-in-oil (O / W) emulsion in which the aqueous phase is a continuous phase and the oil phase is a dispersed phase; and a fourth step: a step of adding a melamine formaldehyde prepolymer compound to the water-in-oil (O / W) emulsion to cause a condensation reaction of the melamine formaldehyde prepolymer compound on the interface of the water-in-oil (O / W) emulsion. a fifth step: a step of separating the microparticles having the organic solvent encapsulated therein from the microparticle dispersion; and a sixth step: a step of removing the organic solvent from the interior of the microparticles to obtain hollow microparticles. The method for producing hollow microparticles according to claim 6 further comprises the steps of: (a) an oil phase containing an organic solvent and (b) an aqueous phase containing a surfactant comprising at least one maleic anhydride copolymer, the weight ratio of which is 100 to 500 parts by mass of the component (b) when the component (a) is 100 parts by mass.
8. 8. The method for producing hollow microparticles according to claim 7, wherein the organic solvent used in the oil phase (a) is selected from organic solvents having a boiling point of 100° C. or higher and 180° C. or lower.
Citation Information
Patent Citations
Preparation of microballoon
JP1995041594A
Method and apparatus for manufacturing polymer foam beads or balloons
JP2008523192A
Hollow microballoons for CMP polishing pad
WO2021201088A1